Concussion among soccer players in the 2017 Brazilian championship – the gap between protocol and medical practice - Cármine Porcelli Salvarani; Lucas Ribeiro de Medeiros; Fernando Henrique Sapatero; Diego Ciotta de Castro; Vinícius Simon Tomazini; Leonardo Henrique Micheletti Sotocorno; Paulo Sérgio Teixeira da Costa; Bruno Bueno Pimenta; Diego Almeida de Oliveira; Eduardo Almeida Dias; Eduardo Vinícius Colman da Silva (Concussion)
Background: The present study aims to report traumatic brain injury (TBI) among soccer players in the 2017 Brazilian Soccer Championship and discuss the protocols for concussion evaluation. Materials & methods: This is an observational study utilizing video analysis of 380 matches. TBI was considered as any event in which one or more soccer player(s) had a head trauma. For potential concussion diagnosis, we analyzed players with one of the following signs: slowness to get up, disorientation, motor incoordination, loss of consciousness, head clutching and impact seizure. Results: There were 374 TBIs in total. The average time for medical assessment was 1′35”. 13 players had concussion with an average time of 3′19″ for medical evaluation. Four players were replaced after having a concussion. Conclusion: There is a gap between concussion protocols and medical practices in Brazilian elite soccer. Further discussion about soccer replacement rules are imperative.